Development of ARSA (Augmented Reality Struktur Atom) Based on Android as an Independent Learning Resource for High School Students - Irfansyah Nabilazuardi Pratama; Erfan Priyambodo (Universitas Negeri Yogyakarta, 2024)
This research aims to determine the characteristics, feasibility, and student responses to the Android-based ARSA as an independent learning resource for high school/Islamic high school (SMA/MA) students. The research method used is a mixed-methods approach with an exploratory sequential design. The data obtained includes qualitative descriptive data in the needs analysis, expert validation test, and peer reviewer feasibility test. For the feasibility test by reviewers and the student response test, qualitative data were converted into quantitative data using a Likert scale and then analyzed using ideal conversion guidelines to determine the feasibility of the product in each aspect and overall. The research results show that the ARSA learning resource has the following characteristics: it features interactive 3D visualizations of atomic models, can be used without an internet connection, and serves as an independent learning resource for SMA/MA students. The ARSA learning resource was declared feasible for use after adjustments were made based on comments/suggestions from prospective teachers as peer reviewers and chemistry teachers as reviewers. It was also declared suitable for use by students.